STRATEGI PENGEMBANGAN EKOWISATA MANGROVE BERBASIS MASYARAKAT DALAM MENARIK KUNJUNGAN WISATAWAN DI KAMPUNG BARU KABUPATEN PENAJAM PASER UTARA - Putri Risky (Sekolah Tinggi Pariwisata Mataram, 2022)
Penajam Paser Utara Mangrove Ecotourism is that implements community based tourism. The number of visitors from 2016 until 2019 has increased and decreased because there are stil shortcomings and weaknesses in the develompent of this tourist attraction. Therefore, a develompment strategy is needed in an effort to attract tourist visits. This study aims to identify development strategies as well as to analyze the supporting and inhibiting factors in developing Community Based tourism of Mangrove Ecotourism in Kampung Baru, Penajam Paser Utara. The research method used is qualitative where this type of research conducts interviews, observations, and direct documentation with key informan and informant and then analyzed with an interactive model. The result of study concluded that the develompent stratefy of community based tourism in Mangrove Ecotourism in attracting tourist visits in Penajam Paser Utara was accrodance with the community based tourism approach, which include involving the community is decision making, ensuring that the community received benefits from tourism activities, and tourism education for local communities. The the factors that supports the CBT develompment strategy are the natural beauty that is still maintained, the local community, and Dinas Kebudayaan dan Pariwisata Penajam Paser Utara. Meanwhile, the obstacles faced were access, lack of budget funds, and the status of land acquisition by the community. The manager of the Kampung Baru Mangrove Ecotourism is expected to develop Ecotourism by providing more appropriate facilities such as gazebos, pavilions, and trash bin for the convenience of visitors. Suggestions to overcome inhibiting factors, managers can work together by involving the community in develoving Kampung Baru Mangrove